Menebar kebaikan bagi lingkungan / Hj. Ani Bambang Yudhoyono ; editor Yulia Ekayanti, Siti Gretiani, Raviyanto - ANI BAMBANG YUDHOYONO, Hj.; Yulia Ekayanti; Siti Gretiani; Raviyanto (Gramedia Pustaka Utama, 2014)
419 hlm. : ilus. ; 21 cm